Roots of social enterprise: entrepreneurial philanthropy, England 1600-1908. Issue 1 (5th February 2018) - MacDonald, Matthew; Howorth, Carole
Abstract : Purpose: Insights into the roots of social enterprise from before the term was adopted are provided by examining histories of charitable service and comparing current understandings of social enterprise. Social enterprise models of welfare provision are evidenced from the seventeenth century onwards. Persistent themes are identified that provide insights for current practice and understanding. Design/methodology/approach: This historiography examines interpretations from 1905 to the present day of examples of welfare provision between two watershed points: 1600, just prior to the Poor Laws and 1908, when the Old Age Pensions Act shifted emphasis in public sector provision. Findings: Activities that would nowadays be termed social enterprise are evidenced in histories of charitable philanthropy covering each century since 1600. Prevailing attitudes uncritically demarcated deserving and undeserving poor. Histories contributed to a heroic narrative of social entrepreneurs, describing activities dependent on well-networked, politically active individuals that rarely continued beyond their involvement. The political environment was recognised to influence the types of organisations, governance and resourcing. Research limitations/implications: The historiography takes examples from three centuries between 1600 and1908 but is not comprehensive. Recurrent themes are identified for further research. Originality/value: Social enterprise is a twenty-first-century label but not a new phenomenon. Identification of prevailing themes provides insights for the understanding of social enterprises in the twenty-first century.